If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1x+3x=0
We simplify the equation to the form, which is simple to understand
1x+3x=0
We move all terms containing x to the left and all other terms to the right.
+1x+3x=0
We simplify left and right side of the equation.
+4x=0
We divide both sides of the equation by 4 to get x.
x=0
| 6(1-3x)-2(2x-1)=18x | | 2.5n=-20 | | 9x-10y=3 | | 3s-8=9 | | 5n+3n+n+5=26 | | 5y=12x-5 | | 3x+9=56-4x | | 3a-b=1 | | a+10=27 | | 10x+1y=8 | | -5(1-5)+(-8x-2)=4x-8x | | -1/2+w=3/5 | | (x-6)+x= | | 23+2x=13 | | 3(2c+3)=2(3c-4) | | 6n-10+4n=-18+10n+14 | | 51-3x=6x+23 | | a+3b=7 | | 13+2x=x+25 | | 3x-18/15 | | 5=4n-6 | | 3w-40-2w+60+w= | | 13x+12=38 | | 4n-6=14 | | 15-12x=51 | | f(x)=10-4x | | 4x+18=x+33 | | -31/3b+b | | 8+6a=-28+24 | | 2(3.5x+6)=2.5x-2 | | 2=9x | | 1/2x+4=-3 |